Early Detection of Microsleep in Motorcycle Helmet Based on Pulse Sensor - Putri Madona; Andres Lumban Tobing (SHM Publisher, 2023)
Microsleep can be defined as a brief condition in which someone unintentionally falls asleep for a few seconds to several minutes. This condition can occur in anyone and poses a high potential risk, especially when engaged in activities that require high concentration, such as driving. To detect and address the potential dangers of microsleep while driving, this research has designed a smart helmet capable of early detection of signs of microsleep and taking actions to awaken the rider. This system uses a pulse sensor connected to an Arduino and placed on the backside of the helmet. Detection of beats per minute (bpm) is crucial to determine whether the rider is drowsy or not. This is essential for providing early warnings to the rider. If the rider's bpm reading is <60, indicating drowsiness, the system activates a vibrator to shake the helmet. If this condition persists for more than 7 seconds, the speaker also activates to play music, which will only stop when the bpm reading is >60. Testing was conducted on 5 test subjects, with each subject undergoing 5 trial tests, resulting in a total of 25 test runs. The results indicate that the designed system is capable of reading microsleep conditions and activating the vibrator and music according to the configured settings.